THE EFFECT OF NUTRITION EDUCATION ON THE ENHANCEMENT OF HEALTHY FOOD KNOWLEDGE OF SCHOOL AGE CHILDREN - Nanik Suhartatik; Akhmad Mustofa; Isnaini Elok Nur Azizah; Merkuria Karyantina; Sri Handayani; Riyani (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Nutrition education is an educational program to increase knowledge and attitudes toward nutrition.Higher nutritional knowledge will affect food consumption attitudes and behaviors. Nutrition educationincludes several activities as part of a two-way communication process for knowledge improvementwhich can help one understand and overcome nutrition problems. This study aims to determine theeffect of nutritional education provision on the enhancement of children's healthy food knowledge andprovide information on the proper and correct consumption of healthy foods in the case of publicelementary school of 16 Purwodadi, Grobogan. In this study, 66 fifth graders were involved asrespondents. The respondents were divided into 2 classes, namely, the education class and the noneducationclass. This research began with a pre-test to collect initial data, followed by provision ofeducation four times over a period of three days for the education class. After 2 months, a post-testwas conducted to collect the final data using online questionnaire. The results showed that theprovision of education did not significantly affect the respondents’ knowledge about healthy food butcould change the consumption behavior for some food. However there was a differences in meanvalue of knowledge after education for some questions. In the true/false questions about junk foods,two results were found to change after giving a nutrition education. Such efforts need to be done toimprove food consumption and consumer behavior along food.Keywords: Nutrition education, fast food, healthy food